Designing of Temporary Waste Storage for Household Waste in the Implementation of the 5S Method at PT X West Java - Ginting, Cindy; Yunita Ismail (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Effective and standard-compliant household waste management is a challenge for the industry. PT X, a vehicle tire manufacturer, produces both industrial and household waste. Despite having a good management system, waste is still temporarily stored in open areas without separation, causing soil contamination, odors, and complaints from external parties. This study aims to calculate the waste generation and volume based on categories to design a Temporary Waste Storage Facility that complies with national regulations and supports the implementation of the 5S method. The implementation of the 5S method will improve the household waste management system at PT X, which will reduce the risk of pollution and improve operational practices in the Household Temporary Waste Storage at PT X. Data collection was conducted over eight days through direct measurements in the field in accordance with SNI 3964:2025. The analysis results showed that waste generation consisted of 622 kg/day of residual waste, 765 kg/day of recyclable waste, and 752 kg/day of organic waste. The average daily volume recorded was 2.600 m³/day of residual waste, 3.182 m³/day of recyclable waste, and 2.088 m³/day of organic waste. Based on this data, the Temporary Waste Storage design includes a zone storage division according to waste type, loading and unloading areas, operational corridors, and Temporary Waste Storage maintenance support items.